Fluid resuscitation of adults with severe falciparum malaria: Effects on acid-base status, renal function, and extravascular lung water - Hanson, J; Lam, S; Mohanty, S; Alam, S; Pattnaik, R; Mahanta, K; Hasan, M; Charunwatthana, P; Mishra, S; Day, N; White, N; Dondorp, A (2013)
Objective: To evaluate the efficacy and safety of liberal fluid resuscitation of adults with severe malaria. DESIGN, Setting, Patients, and Methods:: Twenty-eight Bangladeshi and Indian adults with severe falciparum malaria received crystalloid resuscitation guided by transpulmonary thermodilution (PiCCO) in an intensive care setting. Systemic hemodynamics, microvascular indices and measures of acidosis, renal function, and pulmonary edema were followed prospectively. Results: All patients were hypovolemic (global end-diastolic volume index < 680 mL/m) on enrollment. Patients received a median (range) 3230 mL (390-7300) of isotonic saline in the first 6 hours and 5450 mL (710-13,720) in the first 24 hours. With resuscitation, acid-base status deteriorated in 19 of 28 (68%), and there was no significant improvement in renal function. Extravascular lung water increased in 17 of 22 liberally resuscitated patients (77%); eight of these patients developed pulmonary edema, five of whom died. All other patients survived. All patients with pulmonary edema during the study were hypovolemic or euvolemic at the time pulmonary edema developed. Plasma lactate was lower in hypovolemic patients before (rs = 0.38; p = 0.05) and after (rs = 0.49; p = 0.01) resuscitation but was the strongest predictor of mortality before (chi-square = 9.9; p = 0.002) and after resuscitation (chi-square = 11.1; p < 0.001) and correlated with the degree of visualized microvascular sequestration of parasitized erythrocytes at both time points (rs = 0.55; p = 0.003 and rs = 0.43; p = 0.03, respectively). Persisting sequestration was evident in 7 of 15 patients (47%) 48 hours after enrollment. Conclusions: Lactic acidosis-the strongest prognostic indicator in adults with severe falciparum malaria-results from sequestration of parasitized erythrocytes in the microcirculation, not from hypovolemia. Liberal fluid resuscitation has little effect on this sequestration and does not improve acid-base status or renal function. Pulmonary edema-secondary to increased pulmonary vascular permeability-is common, unpredictable, and exacerbated by fluid loading. Liberal fluid replacement of adults with severe malaria should be avoided. © 2013 by the Society of Critical Care Medicine and Lippincott Williams and Wilkins.